2016
DOI: 10.1007/s11745-016-4200-7
|View full text |Cite
|
Sign up to set email alerts
|

New Role of Hispidulin in Lipid Metabolism: PPARα Activator

Abstract: Hispidulin is a naturally occurring flavonoid isolated from a traditional Chinese medicinal herb, Saussurea involucrata. In this study, the regulating role of hispidulin on the mRNA expression level of enzymes involved in lipid metabolism was examined in vitro and in vivo. Moreover, the in vivo lipid-modulating effect of hispidulin was compared with that of fenofibrate, a classical PPARα agonist. Our results in present study demonstrated that hispidulin can directly bind to and activate PPARα as an agonist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Moreover, higher fat content in the tail than in visceral in Tan sheep breed is attributed to down-regulation of this gene 16 . EHHADH encodes a bifunctional β-oxidation enzyme involved in the peroxisomal fatty acid oxidation 68 . ACSL1 prepares long-chain fatty acids for oxidation through addition of co-enzyme A 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher fat content in the tail than in visceral in Tan sheep breed is attributed to down-regulation of this gene 16 . EHHADH encodes a bifunctional β-oxidation enzyme involved in the peroxisomal fatty acid oxidation 68 . ACSL1 prepares long-chain fatty acids for oxidation through addition of co-enzyme A 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, hispidulin modulates lipid metabolism. Hispidulin directly binds to PPAR-α, and then modulates expression of lipid metabolism enzymes (fatty acid binding protein 1/2, and long chain acyl-CoA synthetase 1) [20]. Recently, it was also reported that hispidulin inhibits adipogenesis via inhibition of PPAR-γ expression [21].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo data suggested that 3-month treatment with hispidulin or fenofibrate in dyslipidaemic rat improved the lipid profile 59 . The related flavone wogonin ( 42 ), commonly extracted from the traditional Chinese medicine Scutellaria baicalensis, showed a somewhat similar pharmacological profile.…”
Section: Natural Products Modulating Pparαmentioning
confidence: 99%